Injection filling material for inducing ordered crystallization of silk fibroin through periodic physical stimulation
Through technical means such as periodic physical stimulation and ethanol induction, directed and ordered crystallized silk fibroin injection filler materials are formed, which solves the problem of tertiary structure regulation of silk fibroin in the existing technology and realizes the intelligent function of the gel.
Patent Information
- Application Number
- CN202411895254.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-21
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to effectively control the tertiary structure of silk fibroin, resulting in the formed gel having uncontrollable isotropic and physical properties.
Through periodic physical stimulation, the transition of silk fibroin from α-type to β-type is induced, and through ethanol induction and rapid freezing treatment, an injection filler material with directional orderly crystallization is formed.
The orderly crystallization of silk fibroin is achieved, forming a gel with regular periodic crystal region arrangement, with more intelligent functions, such as excellent film formation, mechanical properties and skin barrier reconstruction effect.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterials, and in particular to an injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation. Background Art
[0002] Silk fibroin is a biomaterial with excellent biocompatibility and biosafety. It is composed of 18 amino acids and has a five-level structure. Through the regulation of the five-level structure, it is widely used in medicine, daily chemicals, food, agricultural chemicals, etc. In recent years, by regulating the secondary structure of silk fibroin, controlling the transformation of silk fibroin from an α-type amorphous structure to a β-folded structure, the physical properties of silk fibroin solutions have been regulated and applied to different scenarios in the medical field.
[0003] The traditional mechanism of silk fibroin gelation: through physical stimulation, the secondary structure of silk fibroin is promoted to change from α amorphous structure to β anti-folded structure, and finally a tertiary structure of α and β disordered interlaced is formed. Therefore, the final gel is isotropic and its properties are uncontrollable.
[0004] The prior art mostly studies and applies the secondary structure of silk fibroin, that is, by regulating the degree of the β-folding structure of silk fibroin to obtain silk fibroin with suitable physical properties, but does not regulate the tertiary structure of silk fibroin, that is, controlling the orderly arrangement of the crystalline regions of silk fibroin. Based on this, the present invention further improves it. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of the present invention is to provide an injectable filling material that can induce orderly crystallization of silk fibroin by periodic physical stimulation, so as to solve the problems raised in the above-mentioned background technology.
[0006] The present invention solves the technical problem by adopting the following technical solution: the present invention provides an injection filling material that induces orderly crystallization of silk fibroin by periodic physical stimulation, wherein the injection filling material is first subjected to low-frequency directional physical stimulation to induce convergence of the transformation site and transformation direction of the silk fibroin α-type to β-type, thereby forming a tertiary structure in which α-type and β-type are orderly interlaced;
[0007] Then, ethanol is induced to accelerate the stabilization and crystallization of the tertiary structure of silk fibroin, and quick freezing treatment is used to reduce the movement of molecular chains during the gelation process. Finally, the ethanol in the silk fibroin gel is removed by phase separation to finally obtain an injection filling material with directional and orderly crystals.
[0008] Ethanol induction: add the induced silk fibroin solution into ethanol with a concentration higher than 75%;
[0009] Quick freezing treatment: Place the mixed solution in a low-temperature environment below -80 degrees for a certain period of time, such as an ultra-low temperature refrigerator or liquid nitrogen tank;
[0010] Phase separation: The melting point of ethanol is -114.1°C, and the melting point of silk fibroin solution is about 0°C. The solid matter is taken out after quick freezing.
[0011] Preferably, the following steps are adopted in the low-frequency directional physical stimulation:
[0012] Shear: Short-term continuous shear force in the same local direction induces silk fibroin to fold in the tangential direction and form crystals;
[0013] Ultrasound: Induces the production of different forms of ordered crystallized silk fibroin gels according to the ultrasound frequency and the location of the ultrasound source;
[0014] Shaking on a shaker: Shaking on a shaker simulates daily shaking, providing a stimulus for the chaotic state and inducing the production of isotropic silk protein gel;
[0015] Magnetic resonance: Induced generation of silk fibroin gel with emission-like ordered crystals.
[0016] Preferably, the low-frequency directional physical stimulation is preceded by a dissolution treatment of soluble silk protein:
[0017] The specific dissolution treatment method is:
[0018] The silk and the sodium carbonate solution are in a bath ratio of 1:100 to 1:500, the chopped silk is slightly boiled in a sodium carbonate solution with a concentration of 0.01 to 0.5% w / v for 20 to 60 minutes, the sericin on the surface of the silk is washed off with deionized water, the degummed silk is dried at 50 to 80° C. for more than 30 minutes, and the degummed silk is dissolved in a lithium bromide solution at a bath ratio of 9:100 to 30:100 at 40 to 80° C., and after dissolution, it is dialyzed with deionized water for more than 3 days to obtain a silk fibroin solution;
[0019] The silk fibroin solution is treated by immersing in hydroxyapatite for improvement. The specific improvement method is as follows:
[0020] The modified hydroxyapatite is immersed in the silk fibroin solution at a weight ratio of 2:5 for ultrasonic immersion treatment, with an ultrasonic power of 350-400W and an ultrasonic time of 20-30min. When the immersion is completed, the improvement treatment is completed.
[0021] The present invention improves the immersion treatment by adding hydroxyapatite to the existing silk fibroin solution in the dissolution technology, and the modified hydroxyapatite is subjected to heat treatment and potassium permanganate solution treatment to enhance the activity efficiency and dispersion of the hydroxyapatite. Meanwhile, the nano-silicon dioxide in the modified solution is improved by ball milling with raw materials such as phosphate buffer solution and carboxymethyl cellulose, and is permeated with citric acid and chitosan solution, and the improved nano-silicon dioxide is coordinated with hydroxyapatite. The raw materials are coordinated and coordinated, thereby enhancing the subsequent application of the silk fibroin membrane.
[0022] Preferably, the preparation method of the modified hydroxyapatite is:
[0023] S1: heat-treating the hydroxyapatite at 120-130°C for 5-10 minutes, cooling it to 55°C, keeping it warm, adding the kept hydroxyapatite to a sufficient amount of potassium permanganate solution, stirring and mixing it thoroughly, then washing it with water, filtering it with suction, and drying it to obtain a hydroxyapatite agent;
[0024] S2: The hydroxyapatite agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain modified hydroxyapatite.
[0025] Preferably, the stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring is 20-30 min.
[0026] Preferably, the mass fraction of the potassium permanganate solution is 4-7%.
[0027] Preferably, the preparation method of the modified liquid is:
[0028] S11: immersing the nano-silica into a phosphate buffer solution which is 3-5 times the total amount of the nano-silica and mixing well to obtain a nano-silica liquid;
[0029] S12: 3-5 parts of nano-silica liquid, 1-3 parts of nano-silica sol and 2-5 parts of carboxymethyl cellulose are mixed and ball-milled at a speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain modified nano-silica;
[0030] S13: 2-5 parts of silane coupling agent KH550, 1-3 parts of citric acid and 2-4 parts of modified nano-silicon dioxide are added to 6-8 parts of chitosan solution and subjected to ultrasonic treatment to obtain a modified solution.
[0031] Preferably, the pH value of the phosphate buffer solution is 5.5.
[0032] Preferably, the mass fraction of the chitosan solution is 3-6%.
[0033] Preferably, the ultrasonic power of the ultrasonic treatment is 400-500W, and the ultrasonic time is 20-30min.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The present invention provides periodic thermodynamic stimulation to the silk fibroin molecular chain during the process of deconstructing and reconstructing the quinary structure of silk fibroin, so that the silk fibroin can form a regular periodic crystal region arrangement during the process of reconstructing the tertiary structure, thereby making the final formed silk fibroin gel, solution, fiber, scaffold and other materials have more intelligent functions;
[0036] The silk fibroin gel prepared by the present invention can be directed to obtain silk fibroin gels with different properties, such as: the planar crystallized silk fibroin gel has excellent film-forming properties, can quickly form a silk fibroin film when coated on the skin surface, has a bacteriostatic effect, and is used to promote wound healing; the tetrahedral structured silk fibroin gel has excellent mechanical properties, can be used for deep filling, or cartilage repair filling; the snowflake-shaped silk fibroin gel is injected into the superficial layer of the skin, and can form a dense silk fibroin network structure as the water evaporates, which has the effect of rebuilding the skin barrier. DETAILED DESCRIPTION
[0037] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The present embodiment provides an injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation. The injection filling material is first subjected to low-frequency directional physical stimulation to induce convergence of the transformation site and transformation direction of the silk fibroin α-type to β-type, thereby forming a tertiary structure in which α-type and β-type are orderly interlaced.
[0039] Then, ethanol is induced to accelerate the stabilization and crystallization of the tertiary structure of silk fibroin, and quick freezing treatment is used to reduce the movement of molecular chains during the gelation process. Finally, the ethanol in the silk fibroin gel is removed by phase separation to finally obtain an injection filling material with directional and orderly crystals.
[0040] The following steps are adopted in the low-frequency directional physical stimulation of this embodiment:
[0041] Shear: Short-term continuous shear force in the same local direction induces silk fibroin to fold in the tangential direction and form crystals;
[0042] Ultrasound: Induces the production of different forms of ordered crystallized silk fibroin gels according to the ultrasound frequency and the location of the ultrasound source;
[0043] Shaking on a shaker: Shaking on a shaker simulates daily shaking, providing a stimulus for the chaotic state and inducing the production of isotropic silk protein gel;
[0044] In this embodiment, soluble silk protein is also dissolved before the low-frequency directional physical stimulation:
[0045] The specific dissolution treatment method is:
[0046] The silk and the sodium carbonate solution are in a bath ratio of 1:100 to 1:500, the chopped silk is slightly boiled in a sodium carbonate solution with a concentration of 0.01 to 0.5% w / v for 20 to 60 minutes, the sericin on the surface of the silk is washed off with deionized water, the degummed silk is dried at 50 to 80° C. for more than 30 minutes, and the degummed silk is dissolved in a lithium bromide solution at a bath ratio of 9:100 to 30:100 at 40 to 80° C., and after dissolution, it is dialyzed with deionized water for more than 3 days to obtain a silk fibroin solution;
[0047] The silk fibroin solution is treated by immersing in hydroxyapatite for improvement. The specific improvement method is as follows:
[0048] The modified hydroxyapatite is immersed in the silk fibroin solution at a weight ratio of 2:5 for ultrasonic immersion treatment, with an ultrasonic power of 350-400W and an ultrasonic time of 20-30min. When the immersion is completed, the improvement treatment is completed.
[0049] The preparation method of the modified hydroxyapatite of this embodiment is:
[0050] S1: heat-treating the hydroxyapatite at 120-130°C for 5-10 minutes, cooling it to 55°C, keeping it warm, adding the kept hydroxyapatite to a sufficient amount of potassium permanganate solution, stirring and mixing it thoroughly, then washing it with water, filtering it with suction, and drying it to obtain a hydroxyapatite agent;
[0051] S2: The hydroxyapatite agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain modified hydroxyapatite.
[0052] The stirring speed of the stirring modification treatment in this embodiment is 550-750 r / min, and the stirring is 20-30 min.
[0053] The mass fraction of the potassium permanganate solution in this embodiment is 4-7%.
[0054] The preparation method of the modified liquid of this embodiment is:
[0055] S11: immersing the nano-silica into a phosphate buffer solution which is 3-5 times the total amount of the nano-silica and mixing well to obtain a nano-silica liquid;
[0056] S12: 3-5 parts of nano-silica liquid, 1-3 parts of nano-silica sol and 2-5 parts of carboxymethyl cellulose are mixed and ball-milled at a speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain modified nano-silica;
[0057] S13: 2-5 parts of silane coupling agent KH550, 1-3 parts of citric acid and 2-4 parts of modified nano-silicon dioxide are added to 6-8 parts of chitosan solution and subjected to ultrasonic treatment to obtain a modified solution.
[0058] The pH value of the phosphate buffer solution in this example is 5.5.
[0059] The mass fraction of the chitosan solution in this embodiment is 3-6%.
[0060] The ultrasonic power of the ultrasonic treatment in this embodiment is 400-500W, and the ultrasonic time is 20-30min.
[0061] Example 1.
[0062] The present embodiment provides an injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation. The injection filling material is first subjected to low-frequency directional physical stimulation to induce convergence of the transformation site and transformation direction of the silk fibroin α-type to β-type, thereby forming a tertiary structure in which α-type and β-type are orderly interlaced.
[0063] Then, ethanol is induced to accelerate the stabilization and crystallization of the tertiary structure of silk fibroin, and quick freezing treatment is used to reduce the movement of molecular chains during the gelation process. Finally, the ethanol in the silk fibroin gel is removed by phase separation to finally obtain an injection filling material with directional and orderly crystals.
[0064] The following steps are adopted in the low-frequency directional physical stimulation of this embodiment:
[0065] Shear: Short-term continuous shear force in the same local direction induces silk fibroin to fold in the tangential direction and form crystals;
[0066] Ultrasound: Induces the production of different forms of ordered crystallized silk fibroin gels according to the ultrasound frequency and the location of the ultrasound source;
[0067] Shaking on a shaker: Shaking on a shaker simulates daily shaking, providing a stimulus for the chaotic state and inducing the production of isotropic silk protein gel;
[0068] In this embodiment, soluble silk protein is also dissolved before the low-frequency directional physical stimulation:
[0069] The specific dissolution treatment method is:
[0070] Silk and sodium carbonate solution at a bath ratio of 1:100. Cut silk into pieces and boil them in a 0.01% w / v sodium carbonate solution for 20 minutes. Wash the sericin on the surface of the silk with deionized water. Dry the degummed silk at 50°C or above and dissolve it in a lithium bromide solution at 40°C at a bath ratio of 9:100. After dissolution, dialyze with deionized water for more than 3 days to obtain a silk fibroin solution.
[0071] The silk fibroin solution is treated by immersing in hydroxyapatite for improvement. The specific improvement method is as follows:
[0072] The modified hydroxyapatite was immersed in a silk fibroin solution at a weight ratio of 2:5 for ultrasonic immersion treatment, with an ultrasonic power of 350 W and an ultrasonic time of 20 min. When the immersion was completed, the improvement treatment was completed.
[0073] The preparation method of the modified hydroxyapatite of this embodiment is:
[0074] S1: heat-treating the hydroxyapatite at 120°C for 5 minutes, cooling it to 55°C, keeping it warm, adding the kept hydroxyapatite to a sufficient amount of potassium permanganate solution, stirring and mixing it thoroughly, then washing it with water, filtering it with suction, and drying it to obtain a hydroxyapatite agent;
[0075] S2: The hydroxyapatite agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain modified hydroxyapatite.
[0076] The stirring speed of the stirring modification treatment in this embodiment is 550 r / min, and the stirring is performed for 20 min.
[0077] The mass fraction of the potassium permanganate solution in this embodiment is 4%.
[0078] The preparation method of the modified liquid of this embodiment is:
[0079] S11: immersing the nano-silica into a phosphate buffer solution which is 3 times the total amount of the nano-silica and mixing well to obtain a nano-silica liquid;
[0080] S12: 3 parts of nano-silica liquid, 1 part of nano-silica sol and 2 parts of carboxymethyl cellulose are mixed and ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain modified nano-silica;
[0081] S13: 2 parts of silane coupling agent KH550, 1 part of citric acid and 2 parts of modified nano-silica are added to 6 parts of chitosan solution and ultrasonically treated to obtain a modified solution.
[0082] The pH value of the phosphate buffer solution in this example is 5.5.
[0083] The mass fraction of the chitosan solution in this embodiment is 3%.
[0084] The ultrasonic power of the ultrasonic treatment in this embodiment is 400 W, and the ultrasonic time is 20 min.
[0085] Example 2.
[0086] The present embodiment provides an injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation. The injection filling material is first subjected to low-frequency directional physical stimulation to induce convergence of the transformation site and transformation direction of the silk fibroin α-type to β-type, thereby forming a tertiary structure in which α-type and β-type are orderly interlaced.
[0087] Then, ethanol is induced to accelerate the stabilization and crystallization of the tertiary structure of silk fibroin, and quick freezing treatment is used to reduce the movement of molecular chains during the gelation process. Finally, the ethanol in the silk fibroin gel is removed by phase separation to finally obtain an injection filling material with directional and orderly crystals.
[0088] The following steps are adopted in the low-frequency directional physical stimulation of this embodiment:
[0089] Shear: Short-term continuous shear force in the same local direction induces silk fibroin to fold in the tangential direction and form crystals;
[0090] Ultrasound: Induces the production of different forms of ordered crystallized silk fibroin gels according to the ultrasound frequency and the location of the ultrasound source;
[0091] Shaking on a shaker: Shaking on a shaker simulates daily shaking, providing stimulation for the chaotic state and inducing the production of isotropic silk protein gel;
[0092] In this embodiment, soluble silk protein is also dissolved before the low-frequency directional physical stimulation:
[0093] The specific dissolution treatment method is:
[0094] The silk and sodium carbonate solution are in a bath ratio of 1:1:500, the chopped silk is boiled in a sodium carbonate solution with a concentration of 0.5% w / v for 60 minutes, the sericin on the surface of the silk is washed off with deionized water, the degummed silk is dried at 80°C for more than 30 minutes, and dissolved in a lithium bromide solution at 80°C at a bath ratio of 30:100, and after dissolution, it is dialyzed with deionized water for more than 3 days to obtain a silk fibroin solution;
[0095] The silk fibroin solution is treated by immersing in hydroxyapatite for improvement. The specific improvement method is as follows:
[0096] The modified hydroxyapatite was immersed in a silk fibroin solution at a weight ratio of 2:5 for ultrasonic immersion treatment, with an ultrasonic power of 400 W and an ultrasonic time of 30 min. After the immersion was completed, the improvement treatment was completed.
[0097] The preparation method of the modified hydroxyapatite of this embodiment is:
[0098] S1: heat-treating the hydroxyapatite at 130°C for 10 minutes, cooling it to 55°C, keeping it warm, adding the kept hydroxyapatite to a sufficient amount of potassium permanganate solution, stirring and mixing it thoroughly, then washing it with water, filtering it with suction, and drying it to obtain a hydroxyapatite agent;
[0099] S2: The hydroxyapatite agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain modified hydroxyapatite.
[0100] The stirring speed of the stirring modification treatment in this embodiment is 750 r / min, and the stirring is 30 min.
[0101] The mass fraction of the potassium permanganate solution in this embodiment is 7%.
[0102] The preparation method of the modified liquid of this embodiment is:
[0103] S11: immersing the nano-silica into a phosphate buffer solution that is 5 times the total amount of the nano-silica and mixing well to obtain a nano-silica liquid;
[0104] S12: 5 parts of nano-silica liquid, 3 parts of nano-silica sol and 5 parts of carboxymethyl cellulose are mixed and ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain modified nano-silica;
[0105] S13: 5 parts of silane coupling agent KH550, 3 parts of citric acid and 4 parts of modified nano-silica were added to 8 parts of chitosan solution and ultrasonically treated to obtain a modified solution.
[0106] The mass fraction of the chitosan solution in this embodiment is 6%.
[0107] The ultrasonic power of the ultrasonic treatment in this embodiment is 500W, and the ultrasonic time is 30min.
[0108] Example 3.
[0109] The present embodiment is an injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation, characterized in that the injection filling material is first subjected to low-frequency directional physical stimulation to induce convergence of the transformation site and transformation direction of the silk fibroin α-type to β-type, thereby forming a tertiary structure of orderly interlaced α-type and β-type;
[0110] Then, ethanol is induced to accelerate the stabilization and crystallization of the tertiary structure of silk fibroin, and quick freezing treatment is used to reduce the movement of molecular chains during the gelation process. Finally, the ethanol in the silk fibroin gel is removed by phase separation to finally obtain an injection filling material with directional and orderly crystals.
[0111] The following steps are adopted in the low-frequency directional physical stimulation of this embodiment:
[0112] Shear: Short-term continuous shear force in the same local direction induces silk fibroin to fold in the tangential direction and form crystals;
[0113] Ultrasound: Induces the production of different forms of ordered crystallized silk fibroin gels according to the ultrasound frequency and the location of the ultrasound source;
[0114] Shaking on a shaker: Shaking on a shaker simulates daily shaking, providing stimulation for the chaotic state and inducing the production of isotropic silk protein gel;
[0115] In this embodiment, soluble silk protein is also dissolved before the low-frequency directional physical stimulation:
[0116] The specific dissolution treatment method is:
[0117] The silk and sodium carbonate solution are in a bath ratio of 1:300, the chopped silk is slightly boiled in a sodium carbonate solution with a concentration of 0.3% w / v for 40 minutes, the sericin on the surface of the silk is washed off with deionized water, the degummed silk is dried at 65°C for more than 10 minutes, and dissolved in a lithium bromide solution at 60°C at a bath ratio of 9:100, and after dissolution, it is dialyzed with deionized water for more than 3 days to obtain a silk fibroin solution;
[0118] The silk fibroin solution is treated by immersing in hydroxyapatite for improvement. The specific improvement method is as follows:
[0119] The modified hydroxyapatite was immersed in a silk fibroin solution at a weight ratio of 2:5 for ultrasonic immersion treatment, with an ultrasonic power of 370 W and an ultrasonic time of 25 min. When the immersion was completed, the improvement treatment was completed.
[0120] The preparation method of the modified hydroxyapatite of this embodiment is:
[0121] S1: heat-treating the hydroxyapatite at 125°C for 7.5 minutes, cooling it to 55°C, keeping it warm, adding the kept hydroxyapatite to a sufficient amount of potassium permanganate solution, stirring and mixing it thoroughly, then washing it with water, filtering it with suction, and drying it to obtain a hydroxyapatite agent;
[0122] S2: The hydroxyapatite agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain modified hydroxyapatite.
[0123] The stirring speed of the stirring modification treatment in this embodiment is 600 r / min, and the stirring is performed for 25 min.
[0124] The mass fraction of the potassium permanganate solution in this embodiment is 5.5%.
[0125] The preparation method of the modified liquid of this embodiment is:
[0126] S11: immersing the nano-silica into a phosphate buffer solution that is 4 times the total amount of the nano-silica and mixing well to obtain a nano-silica liquid;
[0127] S12: 4 parts of nano-silica liquid, 2 parts of nano-silica sol and 3.5 parts of carboxymethyl cellulose are mixed and ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain modified nano-silica;
[0128] S13: 3.5 parts of silane coupling agent KH550, 2 parts of citric acid and 3 parts of modified nano-silica are added to 7 parts of chitosan solution and ultrasonically treated to obtain a modified solution.
[0129] The pH value of the phosphate buffer solution in this example is 5.5.
[0130] The mass fraction of the chitosan solution in this embodiment is 4.5%.
[0131] The ultrasonic power of the ultrasonic treatment in this embodiment is 450W, and the ultrasonic time is 25min.
[0132] Example 4.
[0133] The present embodiment is an injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation, characterized in that the injection filling material is first subjected to low-frequency directional physical stimulation to induce convergence of the transformation site and transformation direction of the silk fibroin α-type to β-type, thereby forming a tertiary structure of orderly interlaced α-type and β-type;
[0134] Then, ethanol is induced to accelerate the stabilization and crystallization of the tertiary structure of silk fibroin, and quick freezing treatment is used to reduce the movement of molecular chains during the gelation process. Finally, the ethanol in the silk fibroin gel is removed by phase separation to finally obtain an injection filling material with directional and orderly crystals.
[0135] The following steps are adopted in the low-frequency directional physical stimulation of this embodiment:
[0136] Shear: Short-term continuous shear force in the same local direction induces silk fibroin to fold in the tangential direction and form crystals;
[0137] Ultrasound: Induces the production of different forms of ordered crystallized silk fibroin gels according to the ultrasound frequency and the location of the ultrasound source;
[0138] Shaking on a shaker: Shaking on a shaker simulates daily shaking, providing stimulation for the chaotic state and inducing the production of isotropic silk protein gel;
[0139] In this embodiment, soluble silk protein is also dissolved before the low-frequency directional physical stimulation:
[0140] The specific dissolution treatment method is:
[0141] The silk and sodium carbonate solution are in a bath ratio of 1:300, the chopped silk is boiled in a sodium carbonate solution with a concentration of 0.2% w / v for 30 minutes, the sericin on the surface of the silk is washed off with deionized water, the degummed silk is dried at 60°C or above, and dissolved in a lithium bromide solution at 50°C at a bath ratio of 9:100, and after dissolution, it is dialyzed with deionized water for more than 3 days to obtain a silk fibroin solution;
[0142] The silk fibroin solution is treated by immersing in hydroxyapatite for improvement. The specific improvement method is as follows:
[0143] The modified hydroxyapatite was immersed in a silk fibroin solution at a weight ratio of 2:5 for ultrasonic immersion treatment, with an ultrasonic power of 360 W and an ultrasonic time of 25 min. When the immersion was completed, the improvement treatment was completed.
[0144] The preparation method of the modified hydroxyapatite of this embodiment is:
[0145] S1: heat-treating the hydroxyapatite at 125°C for 6 minutes, cooling it to 55°C, keeping it warm, adding the kept hydroxyapatite to a sufficient amount of potassium permanganate solution, stirring and mixing it thoroughly, then washing it with water, filtering it with suction, and drying it to obtain a hydroxyapatite agent;
[0146] S2: The hydroxyapatite agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is filtered and dried to obtain modified hydroxyapatite.
[0147] The stirring speed of the stirring modification treatment in this embodiment is 580 r / min, and the stirring is 25 min.
[0148] The mass fraction of the potassium permanganate solution in this embodiment is 5%.
[0149] The preparation method of the modified liquid of this embodiment is:
[0150] S11: immersing the nano-silica into a phosphate buffer solution that is 4 times the total amount of the nano-silica and mixing well to obtain a nano-silica liquid;
[0151] S12: 4 parts of nano-silica liquid, 2 parts of nano-silica sol and 3 parts of carboxymethyl cellulose are mixed and ball-milled at a speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is filtered and dried to obtain modified nano-silica;
[0152] S13: 3 parts of silane coupling agent KH550, 2 parts of citric acid and 3 parts of modified nano-silica are added to 7 parts of chitosan solution and ultrasonically treated to obtain a modified solution.
[0153] The pH value of the phosphate buffer solution in this example is 5.5.
[0154] The mass fraction of the chitosan solution in this embodiment is 4%.
[0155] The ultrasonic power of the ultrasonic treatment in this embodiment is 420W, and the ultrasonic time is 25min.
[0156] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0157] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation, characterized in that: The injection filling material is first subjected to low-frequency directional physical stimulation to induce convergence of the transformation site and transformation direction of the silk fibroin α-type to β-type, thereby forming a tertiary structure in which the α-type and β-type are orderly interlaced; Then, the tertiary structure of silk fibroin is stabilized and crystallized by ethanol induction, and the movement of molecular chains during gelation is reduced by quick freezing. Finally, the ethanol in the silk fibroin gel is removed by phase separation, and finally an injection filling material with directional and orderly crystallization is obtained. Ethanol induction: add the induced silk fibroin solution into ethanol with a concentration higher than 75%; Quick freezing treatment: Place the mixed solution in a low-temperature environment below -80 degrees for a certain period of time, such as an ultra-low temperature refrigerator or liquid nitrogen tank; Phase separation: The melting point of ethanol is -114.1°C, and the melting point of silk fibroin solution is about 0°C. The solid matter is taken out after quick freezing.
2. The injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation according to claim 1, characterized in that: The following steps were used in low-frequency directed physical stimulation: Shear: Short-term continuous shear force in the same local direction induces silk fibroin to fold in the tangential direction and form crystals; Ultrasound: Induces the production of different forms of ordered crystallized silk fibroin gels according to the ultrasound frequency and the location of the ultrasound source; Shaking on a shaker: Shaking on a shaker simulates daily shaking, providing a way to stimulate the chaotic state and induce the production of isotropic silk protein gel.
3. The injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation according to claim 2, characterized in that: Before the low-frequency directional physical stimulation, soluble silk protein is dissolved: The specific dissolution treatment method is: The silk and the sodium carbonate solution are in a bath ratio of 1:100 to 1:500, the chopped silk is slightly boiled in a sodium carbonate solution with a concentration of 0.01 to 0.5% w / v for 20 to 60 minutes, the sericin on the surface of the silk is washed off with deionized water, the degummed silk is dried at 50 to 80° C. for more than 30 minutes, and dissolved in a lithium bromide solution at 40 to 80° C. at a bath ratio of 9:100 to 30:100, and after dissolution, it is dialyzed with deionized water for more than 3 days to obtain a silk fibroin solution; The silk fibroin solution is treated by immersing in hydroxyapatite for improvement. The specific improvement method is as follows: The modified hydroxyapatite is immersed in the silk fibroin solution at a weight ratio of 2:5 for ultrasonic immersion treatment, with an ultrasonic power of 350-400W and an ultrasonic time of 20-30min. When the immersion is completed, the improvement treatment is completed.
4. The injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation according to claim 2, characterized in that: The preparation method of the modified hydroxyapatite is: S1: heat-treating the hydroxyapatite at 120-130°C for 5-10 minutes, cooling it to 55°C, keeping it warm, adding the kept hydroxyapatite to a sufficient amount of potassium permanganate solution, stirring and mixing it thoroughly, then washing it with water, filtering it with suction, and drying it to obtain a hydroxyapatite agent; S2: The hydroxyapatite agent and the modifying liquid are stirred and modified in a weight ratio of 2:
5. After the stirring is completed, the mixture is filtered and dried to obtain modified hydroxyapatite.
5. The injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation according to claim 4, characterized in that: The stirring speed of the stirring modification treatment is 550-750r / min, and the stirring is 20-30min.
6. The injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation according to claim 4, characterized in that: The mass fraction of the potassium permanganate solution is 4-7%.
7. The injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation according to claim 4, characterized in that: The preparation method of the modified liquid is: S11: immersing the nano-silica into a phosphate buffer solution which is 3-5 times the total amount of the nano-silica and mixing well to obtain a nano-silica liquid; S12: 3-5 parts of nano-silica liquid, 1-3 parts of nano-silica sol and 2-5 parts of carboxymethyl cellulose are mixed and ball-milled at a speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain modified nano-silica; S13: 2-5 parts of silane coupling agent KH550, 1-3 parts of citric acid and 2-4 parts of modified nano-silicon dioxide are added to 6-8 parts of chitosan solution and subjected to ultrasonic treatment to obtain a modified solution.
8. The injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation according to claim 7, characterized in that: The pH value of the phosphate buffer solution is 5.
5.
9. The injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation according to claim 7, characterized in that: The mass fraction of the chitosan solution is 3-6%.
10. The injection filling material for inducing orderly crystallization of silk fibroin by periodic physical stimulation according to claim 7, characterized in that: The ultrasonic power of the ultrasonic treatment is 400-500W, and the ultrasonic time is 20-30min.
Citation Information
Cited By
Absorbable injection filler based on four-phase gradient and preparation method thereof
CN121265858A